Identificação de variação somaclonal em batata (Solanum tuberosum L.) através de marcadores morfológicos - Santiago, Gisele (2007)
The potato (Solanum tuberosum L.) is the fourth culture in economic importance in the world after the wheat, of the maize and the rice. Consequently, the research with this species can bring benefits for a considerable number of people. Tissue culture has contributed in the genetic improvement of the potato in the direction of attainment of free plants of virus and micropropagation of elite genotypes. However, plants regenerated from tissue culture can show variation in agronomic characteristics important. The induced variation by tissue culture is called somaclonal variation. The occurrence of somaclonal variation can be identified in vitro for parameters still auxiliary as the multiplication rate. In field, the use of morphologic markers can be used to identify somaclones. The work had as objective: To evaluate the behavior in vitro of cultivating them of potato Asterix and Macaca through the multiplication rate observed during a period of eight months. Identify variant somaclonais proceeding of the culture in vitro of them cultivate Asterix and Macaca through morphological markers.To evaluate the genotype effect, culture-age effect and the type of explant on the occurrence of somaclones. Multiplication rate was used in the attempt to identify the occurrence of somaclonal variation in cultivating of potato Asterix and Macaca with three sources of explantes (apex stems, stems and callus) and two ages of subculture (70 months-old clone and 12 months-new clone).The morphological characterization of the plants and basic tubercles was effected according to described methodology for COLLARES (2002) based in the minimum describers of the potato (Solanum tuberosum L.). The multiplication rat of cultivating Macaca was greater that of Asterix and the behavior of the multiplication rate of Macaca oscillated between extreme values different of the observed one in Asterix. The rate multiplication depends on cultivar.Through the morphological characterization it was possible to identify that to cultivate them Asterix and Macaca had presented different behavior how much to the stability of the morphologic characteristics when passing for culture in vitro. The explante derived from callus in such a way presented the biggest occurrence of somaclonais variants for the treatments that had included Asterix as Macaca. The age of subculture of 70 months and 12 months had not been adjusted for maintenance of disgnostic characteristics of them to cultivate Asterix and Macaca due to occurrence of somaclones. It was possible to identify variant somaclonais in the treatments that had included Asterix and Macaca through the minimum describers of the potato.